Effects of cold water immersion on knee joint position sense in healthy volunteers - Costello, J. T.; Donnelly, A. E. (Journal of Sports Sciences, 2011)
The purpose of this study was to determine the effects of cryotherapy, in the form of cold water immersion, on knee joint position sense. Fourteen healthy volunteers, with no previous knee injury or pre-existing clinical condition, participated in this randomized cross-over trial. The intervention consisted of a 30-min immersion, to the level of the umbilicus, in either cold (14 ± 1°C) or tepid water (28 ± 1°C). Approximately one week later, in a randomized fashion, the volunteers completed the remaining immersion. Active ipsilateral limb repositioning sense of the right knee was measured, using weight-bearing and non-weight-bearing assessments, employing video-recorded 3D motion analysis. These assessments were conducted immediately before and after a cold and tepid water immersion. No significant differences were found between treatments for the absolute (P = 0.29), relative (P = 0.21) or variable error (P = 0.86). The average effect size of the outcome measures was modest (range -0.49 to 0.9) and all the associated 95% confidence intervals for these effect sizes crossed zero. These results indicate that there is no evidence of an enhanced risk of injury, following a return to sporting activity, after cold water immersion.